Nonadaptive origin of interactome complexity - Fernandez, Ariel (2011)
The boundaries between prokaryotes, unicellular eukaryotes, and multicellular eukaryotes are accompanied by orders-of-magnitude reductions in effective population size, with concurrent amplifications of the effects of random genetic drift and mutation (1). The resultant decline in the efficiency of selection appears to be sufficient to influence a wide range of attributes at the genomic level in a nonadaptive manner (2). A key remaining question concerns the extent to which variation in the power of random genetic drift is capable of explaining phylogenetic diversity at the subcellular and cellular levels (2-4). Should this be the case, population size would have to be considered as a potential determinant of the mechanistic pathways responsible for long-term phenotypic evolution. Here we demonstrate a phylogenetically broad inverse relationship between the power of drift and the structural integrity of protein subunits. This leads to the hypothesis that the accumulation of mildly deleterious mutations in populations of small size induces secondary selection for protein-protein interactions that stabilize key gene functions. Thus, although complex protein architectures and interactions may be essential contributors to phenotypic complexity, such features may initially emerge by nonadaptive mechanisms.